Reviving the Aral Sea: A Hydro‐Eco‐Social Perspective - Xiaolei Wang; Junze Zhang; Shuai Wang; Yongxiao Ge; Zihao Duan; Lin Sun; Michael E. Meadows; Yi Luo; Bojie Fu; Xi Chen; Yue Huang; Xiaoting Ma; et al. (Earth's Future, 2023)
Abstract The rapid shrinkage and salinization of the Aral Sea over the last few decades has precipitated an environmental disaster, with widespread implications for people whose livelihoods depend on it. Although debated extensively, few viable strategies have yet been identified for reviving the Aral Sea. Here, we propose a hydro‐eco‐social framework to develop a viable, sustainable solution and explore its feasibility to resolve the Aral Sea problem. Based on eco‐environmental indicators, we contend that it is feasible to raise the Aral Sea by 40 m above the Baltic Sea level, while maintaining salinity levels tolerable for aquatic organisms, simultaneously reducing sandstorm risk by 58%. Basin‐wide water balance under climate change scenarios shows that this level can be supported through management interventions that reduce water usage by 22.0–23.2 km3/year and ensure sufficient recharge into the lake, without compromising socio‐economic opportunities. To implement this solution, we propose establishing a socio‐ecologically aligned water governance network for basin‐scale water management that has potential application for other, similarly declining, major lake systems.